RELIGIOSITY AS A MODERATOR FOR FRAUD PREVENTION IN VILLAGE FUND MANAGEMENT - Herlinda Charim; Panca Wahyuningsih; Mohklas Mohklas (STIE Pelita Nusantara Semarang, 2023)
This study aims to determine whether the competence of village apparatus, individual morality has an effect on fraud prevention and religiosity as a moderating variable. The population in this study were village officials at the Village Government in the District of Responsibility, Grobogan Regency, Central Java Province. Sampling was carried out using the census method and the number of samples was 106 respondents. Type of data used is primary data. This study uses a questionnaire in data collection. The test technique used is validity test, reliability test, classical assumption test including normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing in this study used the interaction moderation test (MRA) with SPSS version 23.Results of this study indicate that the Competence of the Village Apparatus has a negative and significant effect on Fraud Prevention. Meanwhile, Individual Morality has a positive and significant effect on Fraud Prevention. Religiosity is not able to moderate the influence of Village Apparatus Competence. But Religiosity is able to moderate the influence of Individual Morality on Fraud Prevention in Village Fund Management.